The levels of hs-CRP in patients with coronary heart disease (Faculty of Medicine Universitas Indonesia, 2004)
Coronary heart disease (CHD) due to atherosclerosis is a multifactorial process with multiple interdependent factors. At present time, atherosclerosis is considered to be an inflammatory process. It has been proven that inflammation plays a mayor role in the initiation, progression as well as the destabilitation of the atherosclerosis plaque. High sensitivity C-reactive protein (hs-CRP) is one of the most important inflammatory marker in CHD and directly related to the extent and severity of atherosclerosis, extent of myocardial ischemia and myocardial necrosis. The purpose of this study is to determine hs-CRP levels in patients with acute coronary syndrome (ACS), chronic CHD and non CHD. And, to determine the correlation between hs-CRP levels and CKMB enzyme level in patients with acute myocardial infarction (AMI). This is a descriptive observational analytic study with cross sectional design. hs-CRP levels were measured by using chemiluminescent method on 21 ACS patients, 20 chronic CHD patients and 20 non CHD patients. The mean hs-CRP level in ACS, chronic CHD and non CHD patients were respectively 8.40 (SD 5.53) mg/l, 2.81 (SD 2.09) mg/l and 1.07 (SD 0.81) mg/l. A statistically significant difference in hs-CRP level was found between ACS, chronic CHD and non CHD (p = 0.000). A positive correlation was found between hs-CRP level and CKMB enzyme level in AMI patients (p = 0.004). In conclusion hs-CRP level is consistently higher in patients with ACS compared to patients with chronic CHD and non CHD. A positive correlation was found between the increased level of hs-CRP and CKMB enzyme level. (Med J Indones 2004; 13: 102-6) Keywords: atherosclerosis, inflammation, hs-CRP, CHD